(3eNJUQ GdSjQI GdfHhjIs - (3GHf aGQS , CHh GdMSjf CMeO Hf aGQS Hf RcQjGA GdbRhjfj GdQGRj,J (B395 (3g` s
(3ChdgG (B:s
(3CfHCfG GdTjN Gdabjg GdbGVi CHh GdbGSe YHO GdUeO Hf CHj YHO Gddg eMeO Hf CHj GdaVd GdCfUGQi bGd gPG PcQ eG jMb Ydi GdeQA GdeSde MaXg hjLH Ydi Pi GdOjf eYQaJg ef fSH QShd Gddg Udi Gddg Ydjg hSde hehdOg hefSGg s
(3BNQgG (B:s
(3agPG ChLR eG Cecf ef MOjK ehdOg heHYKg hCMhGdg Udi Gddg Ydjg hSde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B21 - (3U(B26s
(3GdfSNI HgG MhGTs
(3GfXQ Qbe (B" 704" (3JGQjNs
(3Ydi ghGeTgG JbjjOGJs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs